Hematological Response of Tilapia (Oreochromis niloticus) in Laundry Wastewater - Saparuddin Saparuddin; Yanti Yanti; Salim Salim; Harish Muhammad (Biogenesis: Jurnal Ilmiah Biologi, 2020)
The high concentration of detergent in the aquatic ecosystem potentially affects the fish's physiological condition by disrupting the respiration process and changing the concentration of blood components and chemistry. This study aimed to determine the condition of the hematological parameters of tilapia (Oreochromis niloticus) exposed to wastewater from the laundry industry. Each treatment was stocked with five fish per aquarium (50x30x30 cm). This study used a completely randomized design (CRD) technique with treatments include P0 (0%) as a control, P1 (1%), P2 (2%), P3 (3%), P4 (4%), and P5 (5%) with each treatment exposed to a specific concentration of wastewater and residues. The results showed that the hemoglobin levels of treatments decreased, with the lowest mean of hemoglobin level found in the P2 (7.05 gr%), and the lowest concentration on the 30th day was 7.71 gr%. There were no significant effects of wastewater on erythrocytes and leucocytes number among treatments (P > 0.05). While there were increasing hematocrit levels, the largest mean level was found in the P4 treatment with a value of 24.11 gr%, and the largest mean on the 20th day of observation showed a value of 23.51 gr%. Wastewater from the laundry industry can affect tilapia's hematological condition by decreasing the hemoglobin concentration and increasing the hematocrit levels above the normal condition.